2019
DOI: 10.18203/issn.2455-4510.intjresorthop20195791
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of lumbar disc herniations in adults with low back pain in Enugu, Nigeria

Abstract: <p class="abstract"><strong>Background:</strong> Lumbar intervertebral disc herniation is used to describe a spectrum of anatomical abnormalities involving disc extension beyond the interspace. It follows a tear in the annulus fibrosus of the intervertebral disc. It is one of the most common causes of low back pain among adults. The study aims to assess the epidemiological pattern of lumbar disc herniations among adults with low back pain in Enugu urban.</p><p class="abstract"><… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This may be caused by various factors, one of which is the number/area of the affected segment. 5 In this study, it was found that most research subjects had an excessive or abnormal body mass index (overweight and obese), which was 77.5%.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This may be caused by various factors, one of which is the number/area of the affected segment. 5 In this study, it was found that most research subjects had an excessive or abnormal body mass index (overweight and obese), which was 77.5%.…”
Section: Discussionmentioning
confidence: 69%
“…21 In this study, no significant relationship was found between body mass index and the degree of disability in LDH patients as measured using the ODI score (p-value 0.757). 5 Harvard Medical School: Boston.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation